Penerapan Metode Naive Bayes Dalam Menentukan Tingkat Kenyamanan Pada Rumah Sakit Terhadap Pasien - Masduki Nizam Fadli; Irfan Sudahri Damanik; Eka Irawan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The level of security of a hospital is an important value that must be considered, because it can support a faster healing process for patients. To maintain the quality of comfort, doctors, nurses along with caricature in the hospital must always maintain the criteria determined by the hospital so that the better the value of the service. Understanding Comfort is a condition of feeling someone who feels comfortable based on the perception of each individual. Whereas comfort is a condition that has fulfilled the basic human needs of an individual nature due to several environmental conditions. In a large Indonesian dictionary, comfortable means fresh, healthy, delicious, cool, delicious. Naive Bayes is an algorithm of Data Mining where the nature of Naive Bayes itself is a classification which has two stages in the process of text classification, namely the training stage and the testing / classification stage. During the training phase, the process of analyzing the sample documents is in the form of vocabulary selection, which is a word that might appear in the collection of sample documents, as far as possible to be a representation of the document. Next is determining the prior probabilities for each category based on document samples